EMERGENCE OF CARBAPENEM-RESISTANT ACINETOBACTER BAUMANNII IN THE INTENSIVE CARE UNIT OF A REFERRAL HOSPITAL OF EASTERN INDIA AND ITS THERAPEUTIC OPTION - Rit, Kalidas; Chakraborty, Bipasa; Chakrabarty, Parthasarathi (International Journal of Clinical and Biomedical Research, 2015)
Background and objective: Multidrug-resistant Acinetobacter baumannii has one of the most serious nosocomially acquired gram negative infection in Intensive Care Unit (ICU). The gradual increase in incidence of this pathogen reflects their de-novo selection due to antibiotic usages and its ability to spread between patients. This study was undertaken to detect resistance to carbapenems in clinical isolates of A. baumannii in our ICU set up and to assess the rate of carbapenemase and MBL production among the isolates with the therapeutic options available against them. Material and methods: A. baumannii was identified by conventional methodology and susceptibility profile was determined by disc diffusion method. Carbapenem resistant isolates were further checked for mettalo beta lactamases (MBL) assay by EDTA disc synergy test and Minimum inhibitory concentration determination by agar dilution method. Results: 71.87% (n=46) of isolates showed resistance to Imipenem by disc diffusion method. 82.6% (n=38) of isolates were MBL producer both by phenotypic EDTA disc synergy test and MIC determination test by agar dilution method. The susceptibility profiles of A. baumannii strains towards colistin, polymyxin B and tigecycline were 90.62%, 57.81% and 78.12% respectively.Conclusion: Detection as well as awareness of this MBL producing A. baumannii in a hospital set up, coupled with judicious antimicrobial therapy based on sensitivity profiles will help us fight against this deadly menace. KEYWORDS: Acinetobacter baumannii; Carbapenemases; Mettalo beta lactamases.